Ergonomic wireless digital notice board - Wan Isni Sofiah, Wan Din; Boon Li, Tiew; Azlee, Zabidi; Ahmad Firdaus, Zainal Abidin (2021)
This work presents the prototype of ergonomic wireless digital notice board that can be controlled by mobile application installed in Android phone. The prototype is Wi-Fi based and support long distance. Blynk application is used for the development of mobile application. The functionality and performance of the prototype is used to display messages by receiving user input texts and displays input remotely on notice board. At the end of the receiver, a low cost microcontroller board (NodeMCU) is programmed to accept and display messages on notice board. The developed system will therefore aim to share information with intended users and also to save time and cost for paper and printing equipment.